Lenders' Experience with Borrowers' Major Customers and the Debt Contracting Demand for Accounting Conservatism - Gong, Guojin; Luo, Shuqing (The Accounting Review, 2018)
ABSTRACT Lenders often have lending relationships with borrowers' major customers (labeled as “supply-chain lenders”). We hypothesize that private information obtained from borrowers' major customers can facilitate more timely and precise evaluation of borrowers' creditworthiness; this potentially reduces supply-chain lenders' reliance on accounting conservatism in debt contracting. Consistently, we find that suppliers borrowing from supply-chain lenders provide less conservative financial statements than suppliers borrowing from non-supply-chain lenders at loan origination. This finding is more pronounced when supply-chain lenders are likely to have greater information advantage over non-supply-chain lenders. Based on latent factors that proxy for private information accessible from customers, we find that supply-chain lenders' information advantage relates to customers' future operational and financial risks. Further, in lending agreements, supply-chain lenders accept fewer accounting-based contractual terms, lower spreads, and longer loan maturity than non-supply-chain lenders. The overall evidence suggests that borrowers' major customers represent an important information channel that enables lenders to more effectively screen and monitor borrowers, thus weakening the debt contracting demand for accounting conservatism.